2021
DOI: 10.1073/pnas.2100170118
|View full text |Cite
|
Sign up to set email alerts
|

2′-O methylation of RNA cap in SARS-CoV-2 captured by serial crystallography

Abstract: The genome of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) coronavirus has a capping modification at the 5′-untranslated region (UTR) to prevent its degradation by host nucleases. These modifications are performed by the Nsp10/14 and Nsp10/16 heterodimers using S-adenosylmethionine as the methyl donor. Nsp10/16 heterodimer is responsible for the methylation at the ribose 2′-O position of the first nucleotide. To investigate the conformational changes of the complex during 2′-O methyltransfe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 51 publications
1
56
0
Order By: Relevance
“…7f ), an Nsp16 protomer is anchored on the top of an Nsp10 promoter. 307 309 The structure of Nsp10 in the heterodimer does not undergo a significant conformational change, aside from the α1-helix, as previously reported. 125 , 307 , 308 Nsp16 employs a Rossmann-like fold consisting of a centrally located twisted β-sheet of eight β-strands (β1-β8-β9-β6-β7-β2-β3-β4-β5) flanked by α-helices and β-strands.…”
Section: Nonstructural Proteins Of Sras-cov-2supporting
confidence: 74%
See 1 more Smart Citation
“…7f ), an Nsp16 protomer is anchored on the top of an Nsp10 promoter. 307 309 The structure of Nsp10 in the heterodimer does not undergo a significant conformational change, aside from the α1-helix, as previously reported. 125 , 307 , 308 Nsp16 employs a Rossmann-like fold consisting of a centrally located twisted β-sheet of eight β-strands (β1-β8-β9-β6-β7-β2-β3-β4-β5) flanked by α-helices and β-strands.…”
Section: Nonstructural Proteins Of Sras-cov-2supporting
confidence: 74%
“…Ligand-binding sites with unclear functions have also been found on the surface of Nsp16. For example, a positively charged pocket close to the Cap binding pocket, possibly used to bind longer RNA, has been identified; 307 , 309 on the back of the conservative catalytic center (Lys46-Asp130-Lys170-Glu203), 310 , 311 there is another ligand-binding pocket that accommodates adenosine and other small molecules with a heterocyclic ring. 272 , 307 The interface of Nsp16-Nsp10, composed of multiple hydrophobic interactions and hydrogen bonds, largely overlaps with the interface of Nsp14-Nsp10.…”
Section: Nonstructural Proteins Of Sras-cov-2mentioning
confidence: 99%
“…First, it was shown that the putative RNA binding site is a large canyon, localized mostly on the nsp16 subunit (Figure 4 ). Modeling revealed that approximately five nucleotides can occupy the RNA binding channel, positioning the ribose 2′ hydroxyl group within close proximity to the SAM methyl group ( 38 , 40 , 42 ).…”
Section: Introductionmentioning
confidence: 99%
“…Further insights were obtained from a series of crystal structures of this 2′- O -MTase in complex with the methyl donor SAM and the accepting cap-0 analog captured by serial crystallography at room temperature ( 42 ). This study was able to capture three states (i) cap-0 bound, (ii) cap-0 and SAM bound and (iii) cap-1 and SAH ( S -adenosyl- l -homocysteine) bound.…”
Section: Introductionmentioning
confidence: 99%
“… [21] Most of the data obtained by X‐ray crystallography and/or cryo‐EM have the amino acid sequences but hydrogen atom positions are not there. [ 17 , 22 , 23 ] Thus, subsequent computational studies on these structures are needed to provide fine details of interactions, binding affinity and underlying mechanisms of biological functions. [ 22 , 24 , 25 ] Such kind of detailed experimental‐computational joint data are so far lacking for the new variants of SARS‐CoV‐2 quantifying their impact on the virulence.…”
Section: Introductionmentioning
confidence: 99%